Agriculture in Argentina at the start of the millenium: successes and challenges - Reca, Lucio G.; Parellada, G. H. (2001)
The economic program initiated in April of 1991 introduced deep political and institutional reforms that directly affected the farming sector. The central goal of this study is to examine the transformations that took place in the farming sector in response to the macroeconomic changes introduced in the last decade, It also analyzes the way in which is analyzed the sector is facing the challenges that derive from the process of globalization, from the recent and significant scientific and technological advances and from the persistent and diverse forms of commercial protectionism. It includes a brief historical analysis that illustrates the levels of development reached by the Argentine agriculture in the Thirties, its subsequent decline and the unfolding and origin of the changes in productivity that have taken place lately. The analysis of these latter transformations allows to observe the importance that active sectoral policies, in particular, in the innovation system had had for its recent development.